A synthesis of porous activated carbon materials derived from vitamin B9 base for CO2 capture and conversion. (June 2021) - Wang, X.; Hui, W.; Hu, A.; Li, X.; Li, Y.; Wang, H.
Abstract: CO2 capture and conversion are still a favorable way to reduce CO2 in the atmosphere. Herein, we have developed an environmentally friendly, low energy consumption porous activated carbon from vitamin B9 carbonaceous material for CO2 capture and conversion materials. It is demonstrated that the KOH/vitamin B9 carbonaceous material impregnation ratio of 2 is the optimum condition for obtaining porous activated carbons with high specific surface area of 1903 m 2 g -1, micropore surface area of 710 m 2 g -1, total pore volume of 1.05 cm 3 g -1 and micropore volume of 0.38 cm 3 g -1 . Among all the porous activated carbons prepared, the porous activated carbon synthesized with the KOH/vitamin B9 carbonaceous material impregnation ratio of 2 registers the most excellent CO2 capture for 5.41 mmolg −1 at 0 °C/1 bar and 3.66 mmolg −1 at 25 °C/1 bar. They can also effectively catalyze the cycloaddition of CO2 and epoxides under mild conditions (1 bar, 100 °C and 8 h) with a yield of 89–94%. The synthesized porous carbon materials from vitamin B9 is a promising candidate material for CO2 capture and fixation. Highlights: Micropores in porous activated carbon materials play a very positive role in CO2 capture. A large amount of nitrogen will be vanished during the activation process. Nitrogen-rich carbon materials have a favorable promoting effect on the cycloaddition of CO2 and epoxide.